Bias corrected empirical Bayes confidence intervals for the selected mean. Issue 3 (1st February 2019) - Bhattacharjee, Abhishek; Ghosh, Malay
ABSTRACT: Empirical Bayes (EB) methods are very useful for post selection inference. Following Datta et al. (2002 ), we construct EB confidence intervals for the selected population mean. The EB intervals are adjusted to achieve the target coverage probabilities asymptotically up to the second order. Both unconditional coverage probabilities of EB intervals and corresponding probabilities conditional on ancillary statistics are found.